The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1590/s1516-89132001000100013
|View full text |Cite
|
Sign up to set email alerts
|

Studies on probiotics properties of two lactobacillus strains

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 6 publications
3
14
0
2
Order By: Relevance
“…When these values were compared to control (MRS), no statistical difference was observed p˂0.05. These results are in accordance with some studies that reported a doubling time of about 1 h for lactobacilli (Brizuela et al, 2001;Ayeni et al, 2011;Rezvani et al, 2016).…”
Section: Growth Of the Lactobacillus Speciessupporting
confidence: 93%
See 1 more Smart Citation
“…When these values were compared to control (MRS), no statistical difference was observed p˂0.05. These results are in accordance with some studies that reported a doubling time of about 1 h for lactobacilli (Brizuela et al, 2001;Ayeni et al, 2011;Rezvani et al, 2016).…”
Section: Growth Of the Lactobacillus Speciessupporting
confidence: 93%
“…The MRS broth was used as a control. Parameters related to growth as doubling time (g) and specific growth rates (μ) were calculated (Brizuela et al, 2001;Georgieva et al, 2014).…”
Section: Preparation Of Modified Man Rogosa and Sharpe (Mrs) Media Smentioning
confidence: 99%
“…Usually, an incubation time of 12 h is applied. However, in this work we have used lower incubation time (1 h) to avoid exceeding the generation time of LAB and yeasts, which according to the literature, in optimal conditions, is approximately 1.1 h for many species of LAB, and 2 h for the growth-faster yeast species (Brizuela et al 2001;Nagpal and Kaur 2011;Willey et al 2011). In this way, duplication of the microorganisms that are released is prevented and time is reduced.…”
Section: Enzymatic Methodsmentioning
confidence: 99%
“…Contrarily, a very poor prebiotic effect was reported for inulin by Shin et al (2000), likely due to the use of a particular Bifidobacterium strain. Also in this respect, reference to lactobacilli is very poor, and only a few attempts were made in pure cultures of L. acidophilus (Brizuela, Serrano, & Pé rez, 2001;Chou & Weimer, 1999;Du Plessis, Dicks, Vescovo, Torriani, & Dellaglio, 1996;Ordonez, Fung, & Jeon, 2000), Lactobacillus rhamnosus (Goldin, 1998;Jyoti, Suresh, & Venkatesh, 2004), Lactobacillus bulgaricus (Kimmel & Roberts, 1998;RadkeMitchell & Sandine, 1986), Lactobacillus plantarum and L. casei (Gonzá lez, Domínguez-Espinosa, & Alcocero, 2008).…”
Section: Introductionmentioning
confidence: 99%